2017
DOI: 10.4238/gmr16039708
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Atherosclerosis: analysis of the eNOS (T786C) gene polymorphism.

Abstract: ABSTRACT. The coronary arteriosclerotic disease is the most common cardiovascular disease. Atherosclerosis affects large-and medium-sized arteries leading to severe thrombosis or artery stenosis that could evolve to myocardial infarction, ischemic stroke, ischemic injury of kidneys and intestines, and several other life-threatening clinical manifestations. Nitric oxide has been shown to be a promising therapeutic agent against cardiovascular diseases. The eNOS gene assumes several important functions, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…NO produced by the activity of eNOS modulate, beyond other functions, the degree of constriction experienced by a blood vessel, cell cycle progression, senescence or apoptosis, immune system cells activity and platelet aggregation [51][52][53][54][55]. Moreover, availability of NO influences cancer, genomic stability and cardiovascular diseases [31,39,56,57]. Regarding the p53 protein, which is coded by the TP53 gene, is known as the guardian of the genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NO produced by the activity of eNOS modulate, beyond other functions, the degree of constriction experienced by a blood vessel, cell cycle progression, senescence or apoptosis, immune system cells activity and platelet aggregation [51][52][53][54][55]. Moreover, availability of NO influences cancer, genomic stability and cardiovascular diseases [31,39,56,57]. Regarding the p53 protein, which is coded by the TP53 gene, is known as the guardian of the genome.…”
Section: Resultsmentioning
confidence: 99%
“…High cholesterol levels, hypertension, diabetes, smoking and other environmental factors lead to a severe pro-inflammatory and a prothrombotic endothelial state [23][24][25][26][27][28]. In addition, genetic polymorphisms influence endothelial dysfunction because several genes and the proteins they code for, exert crucial functions in regulating vascular endothelial stability [29][30][31]. The eNOS gene regulates the levels of nitric oxide, which is vital for several intracellular biological functions, such as vasodilation, vascular homeostasis, protection of arteries against injuries, cellular growth, signaling pathways and immune response among others [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in diabetics, it strengthens in this way, the knowledge that the regulation of eNOS becomes is critical for protection against atherosclerosis (Bonomini et al, 2008). In our previous work, our research group showed that the presence of multiple risk factors increased the deleterious effects of the C allele regarding the eNOS (T786C) gene polymorphism (Barbosa et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…NO plays an important role in the normal physiology of the cardiovascular system, and dysfunctional NO signaling has been associated with development and progression of cardiovascular diseases -myocardial infarction, coronary spasm, intra-stent thrombosis, heart failure (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%